ChemInform Abstract: An Efficient and Mild Oxidant for the Synthesis of S‐Tetrazines. Issue 4 (January 2015) - Selvaraj, Ramajeyam; Fox, Joseph M.
Abstract Diacetoxyiodobenzene is found to be a mild and efficient oxidant for the oxidation of 1, 4‐dihydro‐s‐tetrazines to s‐tetrazines.